Biomaterial surfaces self-defensive against bacteria by contact transfer of antimicrobials. (June 2019) - Liang, Jing; Wang, Hongjun; Libera, Matthew
Abstract: Despite extensive engineering of tissue-contacting biomedical devices to control healing, these devices remain susceptible to bacterial colonization, biofilm formation, and chronic infection. The threat of selecting for resistance genes largely precludes sustained antimicrobial elution as a wide-spread clinical solution. In response, self-defensive surfaces have been developed where antimicrobial is released only when and where there is a bacterial challenge. We explore a new self-defensive approach using anionic microgels into which small-molecule cationic antimicrobials are loaded by complexation. We identify conditions where antimicrobial remains sequestered within the microgels for periods as long as weeks. However, bacterial contact triggers release and leads to local bacterial killing. We speculate that the close proximity of bacteria alters the local thermodynamic environment and interferes with the microgel-antimicrobial complexation. The contact-transfer approach does not require bacterial metabolism but instead appears to be driven by differences between the microgels and the bacterial cell envelope where there is a high concentration of negative charge and hydrophobicity. Contact with metabolizing macrophages or osteoblasts is, however, insufficient to trigger antimicrobial release, indicating that contact transfer can be specific to bacteria and suggesting an avenue to biomedical device surfaces that can simultaneously promote healing and resist infection.